N-Ribosyltransferase From Archaeoglobus veneficus: A Novel Halotolerant and Thermostable Biocatalyst for the Synthesis of Purine Ribonucleoside Analogs - Acosta, Javier; Del Arco, Jon; Pisabarro, Victor; Gago, Federico; Fernández-Lucas, Jesús (Frontiers in Bioengineering and Biotechnology, 2020)
Nucleoside-2′-deoxyribosyl-transferases (NDTs) catalyze a transglycosylation reaction consisting of the exchange of the 2′-deoxyribose moiety between a purine and/or pyrimidine nucleoside and a purine and/or pyrimidine base. Because NDTs are highly specific for 2′-deoxyribonucleosides they generally display poor activity on modified C2′ and C3′ nucleosides and this limits their use as biocatalysts for the synthesis of modified nucleosides. We now report the production and purification of a novel NDT from Archaeoglobus veneficus that is endowed with native ribosyltransferase activity and hence it is more properly classified as a N-ribosyltransferase (AvNRT). Biophysical and biochemical characterization revealed that AvNRT is a homotetramer that displays maximum activity at 80 ºC and pH 6 and shows remarkably high stability at high temperatures (60-80 ºC). In addition, the activity of AvNRT was found to increase up to 2-fold in 4 M NaCl aqueous solution and is retained in the presence of several water-miscible organic solvents. For completeness, and as a proof of concept for possible industrial applications, this thermophilic and halotolerant biocatalyst was successfully employed in the synthesis of different purine ribonucleoside analogues.